Temporal trends in childhood leukaemia incidence following exposure to radioactive fallout from atmospheric nuclear weapons testing. - Wakeford, R; Darby, S; Murphy, M (2010)
Notably raised rates of childhood leukaemia incidence have been found near some nuclear installations, in particular Sellafield and Dounreay in the United Kingdom, but risk assessments have concluded that the radiation doses estimated to have been received by children or in utero as a result of operations at these installations are much too small to account for the reported increases in incidence. This has led to speculation that the risk of childhood leukaemia arising from internal exposure to radiation following the intake of radioactive material released from nuclear facilities has been substantially underestimated. The radionuclides discharged from many nuclear installations are similar to those released into the global environment by atmospheric nuclear weapons testing, which was at its height in the late-1950s and early-1960s. Measurements of anthropogenic radionuclides in members of the general public resident in the vicinity of Sellafield and Dounreay have found levels that do not differ greatly from those in persons living remote from nuclear installations that are due to ubiquitous exposure to the radioactive debris of nuclear weapons testing. Therefore, if the leukaemia risk to children resulting from deposition within the body of radioactive material discharged from nuclear facilities has been grossly underestimated, then a pronounced excess of childhood leukaemia would have been expected as a consequence of the short period of intense atmospheric weapons testing. We have examined childhood leukaemia incidence in 11 large-scale cancer registries in three continents for which data were available at least as early as 1962. We found no evidence of a wave of excess cases corresponding to the peak of radioactive fallout from atmospheric weapons testing. The absence of a discernible increase in the incidence of childhood leukaemia following the period of maximum exposure to the radioactive debris of this testing weighs heavily against the suggestion that conventional methods are seriously in error when assessing the risk of childhood leukaemia from exposure to man-made radionuclides released from nuclear installations.